«OROLBO‘YI» MILLIY TABIAT BOG‘IDA OLIB BORILGAN BAHORGI VA YOZGI ORNITOLOGIK KUZATISHLAR - Abdikarimova, M.K.; Jumanov , M.A.; Nurimov , B.J.; Bekniyazova, D.B.; Tleumuratov, S.A. (Actual problems and prospects of the study of the fauna, 2024)
The article describes the materials of ornithological research conducted in the Aral region National Natural Park and its surroundings in spring and summer of 2024. The species composition, distribution, number and ecology of some species of birds have been studied by the authors.